The effect of Back Exercise to Low Back Pain Perception of Elderly in Banjar Pande Sumerta Kaja Village 2012 - Purna Jiwa, IGNM (Coping: Community of Publishing in Nursing; Vol 1 No 2 (2013): JURNAL EDISI JULI-DESEMBER 2013, 2013)
Aging Process in elderly most effect problems of musculoskeletal system, such as low back pain. If low back pain in the elderly are not treated, there will be paralysis. The goal of this study is to describe the effect of back exercise to low back pain perception of elderly. This study is one group pre-post test design pre-experimental study without control group. This group of subject will be observed before the intervention, then will be observed again after the last intervention. Sample size used was 21 elders. Collection of data needed was done by Interview sheets of Numerical Rating Scale (NRS) that analyzed with Wilcoxon Test with significancy p?0,05. Wilcoxon Test result value of p=0,000 means there are effect back exercise to low back pain perception in elders. Based on these results, it is suggested to the nurse of comunity health to use this back exercise as an complementary therapy in the treatment of low back pain in elderly.
Keywords: Low Back Pain, Back Exercise, Elderly